Risk of hepato‐pancreato‐biliary cancer is increased by primary sclerosing cholangitis in patients with inflammatory bowel disease: A population‐based cohort study. Issue 2 (2nd February 2022) - Yu, Jingru; Refsum, Erle; Helsingen, Lise M.; Folseraas, Trine; Ploner, Alexander; Wieszczy, Paulina; Barua, Ishita; Jodal, Henriette C.; Melum, Espen; Løberg, Magnus; Blom, Johannes; Bretthauer, Michael; et al.
Abstract: Background: There is continued uncertainty regarding the risks of hepato‐pancreato‐biliary cancers in patients with inflammatory bowel disease (IBD) with or without concomitant primary sclerosing cholangitis (PSC). Objective: To give updated estimates on risk of hepato‐pancreato‐biliary cancers in patients with IBD, including pancreatic cancer, hepatocellular carcinoma, gall bladder cancer, and intra – and extrahepatic cholangiocarcinoma. Methods: In a population‐based cohort study, we included all patients diagnosed with IBD in Norway and Sweden from 1987 to 2016. The cohort comprised of 141, 960 patients, identified through hospital databases and the National Patient Register. Participants were followed through linkage to national cancer, cause of death, and population registries. We calculated absolute risk and standardized incidence ratios (SIRs) of hepato‐pancreato‐biliary cancers by PSC and other clinical characteristics. Results: Of the 141, 960 IBD patients, 3.2% were diagnosed with PSC. During a median follow‐up of 10.0 years, we identified 443 biliary tract cancers (SIR 5.2, 95% confidence interval [CI] 4.8–5.7), 161 hepatocellular carcinomas (SIR 2.4, 95% CI 2.0–2.7) and 282 pancreatic cancers (SIR 1.3, 95% CI 1.2–1.5). The relative risks were considerably higher in PSC‐IBD patients, with SIR of 140 (95% CI 123–159) for biliary tract, 38.6 (95% CI 29.2–50.0) for hepatocellular, and 9.0 (95% CI 6.3–12.6) for pancreatic cancer. The SIRs were still slightly increased in non‐PSC‐IBD patients, compared to the general population. For biliary tract cancer, the cumulative probability at 25 years was 15.6% in PSC‐IBD patients, and 0.4% in non‐PSC‐IBD patients. Conclusions: The dramatically increased risks of hepato‐pancreato‐biliary cancers in PSC‐IBD patients support periodic surveillance for these malignancies. While much lower, the excess relative risks in non‐PSC‐IBD patients were not trivial compared to non‐IBD related risk factors.